Origin and Evolution of the Sodium -Pumping NADH: Ubiquinone Oxidoreductase - Reyes-Prieto, Adrian (Public Library of Science, 2014)
The sodium -pumping NADH: ubiquinone oxidoreductase (Na(+)-NQR) is the main ion pump and the primary entry site for electrons into the respiratory chain of many different types of pathogenic bacteria. This enzymatic complex creates a transmembrane gradient of sodium that is used by the cell to sustain ionic homeostasis, nutrient transport, ATP synthesis, flagellum rotation and other essential processes. Comparative genomics data demonstrate that the nqr operon, which encodes all Na(+)-NQR subunits, is found in a large variety of bacterial lineages with different habitats and metabolic strategies. Here we studied the distribution, origin and evolution of this enzymatic complex. The molecular phylogenetic analyses and the organizations of the nqr operon indicate that Na(+)-NQR evolved within the Chlorobi/Bacteroidetes group, after the duplication and subsequent neofunctionalization of the operon that encodes the homolog RNF complex. Subsequently, the nqr operon dispersed through multiple horizontal transfer events to other bacterial lineages such as Chlamydiae, Planctomyces and α, β, γ and δ -proteobacteria. Considering the biochemical properties of the Na(+)-NQR complex and its physiological role in different bacteria, we propose a detailed scenario to explain the molecular mechanisms that gave rise to its novel redox- dependent sodium -pumping activity. Our model postulates that the evolution of the Na(+)-NQR complex involved a functional divergence from its RNF homolog, following the duplication of the rnf operon, the loss of the rnfB gene and the recruitment of the reductase subunit of an aromatic monooxygenase.